INCLUSIVE ART PEDAGOGY: KAZAKH CRAFT TRADITIONS IN THE DEVELOPMENT OF CREATIVE POTENTIAL - Esimbek M. Zh.; Rakhmetova N.B. (Interdisciplinary Science Studies, 2025)
This study examines the development of creative potential among students with special educational needs through the integration of inclusive art pedagogy, digital technologies, and Kazakh craft traditions. Using a systematic review of 32 publications indexed in Scopus, the research analyzes global trends, methodological approaches, and thematic directions in contemporary scholarship from 2000 to 2025. Cluster analysis conducted with VOSviewer revealed four dominant research domains: inclusive learning experiences, art and design-based education, digital innovation, and collaborative creativity. Geographical and temporal mapping further demonstrated significant disparities in research distribution and a marked increase in publication activity after 2020, driven by digital transformation and the growing recognition of creativity as a key 21st-century competency. The findings show that artistic practices especially those rooted in cultural heritage play a crucial role in fostering divergent thinking, emotional expression, and social inclusion among SEN learners. Kazakh traditional crafts, characterized by tactile and symbolic richness, offer unique opportunities for culturally responsive creative development. The study concludes that effective enhancement of creative potential in inclusive settings requires holistic, interdisciplinary, and culturally grounded pedagogical models that integrate art, technology, and national craftsmanship